Improving on-farm mixing efficiency - Goodband, Robert D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Particle size reduction has a great impact on efficiency of feed utilization. Decreasing particle size improves digestibility of nutrients by increasing surface area and allowing for greater interaction with digestive enzymes. In addition, particle size reduction can influence how uniformly feed is mixed and potential for segregation of ingredients. Mixing equipment and times also need to be evaluated to ensure feed uniformity. Very often suggested mixing times underestimate the amount of time necessary to thoroughly mix feed. Items such as worn paddles or ribbons, ribbon or paddle speed, and overfilling mixers increase the time necessary for adequate feed mixing and uniformity. The consequences of undermixed feed will be observed in poorer feed conversion. This will be most evident in younger or limit-fed pigs. A mixing efficiency test is a simple procedure to check if your feed is adequately mixed and, therefore, should be used as an indicator of feed quality control.
Keywords: Swine; Diet; Process; Swine